Dephraseologische Ableitungen von deutschen Funktionsverbgefügen und ihre Wiedergabe im Polnischen - Konieczna, Hanka (Studia Germanica Posnaniensia, 2018)
This article discusses the share of constant non-idiomatic syntagms of the Funktionsverbgefüge (FVG) type in German in the formation of noun, adjective and verbal constructions for word formation, e.g. "in Angriff nehmen" > "Inangriffnahme", "die Aufsicht haben" > "aufsichthabend", "Gewähr leisten" > "gewährleisten". This kind of dephraseological derivates, contributing on the one hand to the further development of the nominal style though creation of secondary nominalizations, and on the other hand, illustrating univerbal tendencies, was submitted to the analysis from the word-formation point of view (with taking into consideration of their meaning classification in case of nominal formations). Then the author gave Polish equivalents to the German derivates of FVG. Because of the fact that only a part of the German FVG has congruent or partly congruent equivalents in Polish and because of the differences in the use of particular word-formation structures in both languages, structural analogies could only be observed in not very many cases.